2010
DOI: 10.1083/jcb.200909005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore alignment within the metaphase plate is regulated by centromere stiffness and microtubule depolymerases

Abstract: An automated, quantitative 4D image analysis method is used to track kinetochore dynamics in metaphase cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
208
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(233 citation statements)
references
References 45 publications
25
208
0
Order By: Relevance
“…It revealed that metaphase sister-kinetochore pairs undergo semiregular oscillations along the spindle axis, a phenomenon that had been previously described in a qualitative manner (Skibbens et al, 1993). Our automated assay further showed that the speed of kinetochore movements is controlled antagonistically by two microtubule-depolymerases located at kinetochores, the kinesins MCAK and Kif18a, consistent with previous studies on Kif18a (Jaqaman et al, 2010;Stumpff et al, 2008). However, the depletion of either depolymerase did not affect the semi-regularity of sister-kinetochore oscillations, indicating that other components must be controlling the regularity of chromosome movements.…”
Section: Kinetochores Key Drivers Of Chromosome Movementssupporting
confidence: 90%
See 2 more Smart Citations
“…It revealed that metaphase sister-kinetochore pairs undergo semiregular oscillations along the spindle axis, a phenomenon that had been previously described in a qualitative manner (Skibbens et al, 1993). Our automated assay further showed that the speed of kinetochore movements is controlled antagonistically by two microtubule-depolymerases located at kinetochores, the kinesins MCAK and Kif18a, consistent with previous studies on Kif18a (Jaqaman et al, 2010;Stumpff et al, 2008). However, the depletion of either depolymerase did not affect the semi-regularity of sister-kinetochore oscillations, indicating that other components must be controlling the regularity of chromosome movements.…”
Section: Kinetochores Key Drivers Of Chromosome Movementssupporting
confidence: 90%
“…Microtubule motors, in particular the kinesin CENP-E and dynein, control the movements in this initial phase (Kapoor et al, 2006;Vorozhko et al, 2008). In a second step, once kinetochore pairs are attached in a bipolar manner, chromosome movements are driven by changes in the dynamics of kinetochore-microtubules (Jaqaman et al, 2010;Tirnauer et al, 2002). However, the mechanisms by which kinetochores control plus-end microtubule dynamics have only started to emerge recently.…”
Section: Kinetochores Key Drivers Of Chromosome Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…KIF18A can also make tubulin rings 113 and has an extended loop-2 reminiscent of the kinesin-13 family (BOX 2), which supports the idea that it can bend tubulin to drive depolymerization. These effects on microtubule dynamics likely cause the reported changes in the speed and amplitude of kinetochore oscillations following depletion of KIF18A, and the resulting severe chromosome congression defect 106,114,115 . The first single molecule mechanics data for KIF18A were recently reported,…”
Section: Kinetochore-mediated Pushing and Pullingmentioning
confidence: 99%
“…During mitosis many, but not all, of these proteins localise to the plus end of kinetochore microtubules indicative of a conserved mitotic function. Suppressing the expression or deleting these motors leads an increase in mitotic spindle length, a failure of chromosomes to align on the metaphase plate and a protracted delay in the onset of anaphase, due to activation of the spindle assembly checkpoint (Straight et al 1998;Rischitor et al 2004;Goshima et al 2005;Mayr et al 2007;Stumpff et al 2008;Wargacki et al 2010;Jaqaman et al 2010). During early mitosis, sister kinetochore pairs undergo rapid and co-ordinated oscillations, alternating between moving towards and away from the spindle pole (Skibbens et al 1993;Rieder and Salmon 1994).…”
Section: Introductionmentioning
confidence: 99%